The City and The Plague - Salmin, Leonid (project baikal, 2019)
The article is devoted to the historical impact of plague epidemics on the life of such type of settlements as the city. The plague is considered not so much as a medical and sanitary-technical problem as a transtemporal cultural text related to the phenomena of the city’s social destruction, including nowadays. The article features the phenomenon of today’s “information plague”, which is spreading among present-day citizens at a speed of medieval plague fleas due to mobile means of communication and the Internet.
Keywords: city; plague; crisis of urbanization; quarantine; ghetto; social destruction; theatricalization; dance; carnival; social plague; information manipulations.